ALMA Observations of Supernova Remnant N49 in the Large Magellanic Cloud. II. Non-LTE Analysis of Shock-heated Molecular Clouds - Sano, H.; Yamane, Y.; van Loon, J. Th; Furuya, K.; Fukui, Y.; Alsaberi, R. Z.E.; Bamba, A.; Enokiya, R.; Filipović, M. D.; Indebetouw, R.; Inoue, T.; Kawamura, A.; et al. (Astrophysical Journal, 2023)
We present the first compelling evidence of shock-heated molecular clouds associated with the supernova remnant (SNR) N49 in the Large Magellanic Cloud (LMC). Using 12CO(J = 2-1, 3-2) and 13CO(J = 2-1) line emission data taken with the Atacama Large Millimeter/Submillimeter Array, we derived the H2 number density and kinetic temperature of eight 13CO-detected clouds using the large velocity gradient approximation at a resolution of 3.″5 (∼0.8 pc at the LMC distance). The physical properties of the clouds are divided into two categories: three of them near the shock front show the highest temperatures of ∼50 K with densities of ∼500-700 cm−3, while other clouds slightly distant from the SNR have moderate temperatures of ∼20 K with densities of ∼800-1300 cm−3. The former clouds were heated by supernova shocks, but the latter were dominantly affected by the cosmic-ray heating. These findings are consistent with the efficient production of X-ray recombining plasma in N49 due to thermal conduction between the cold clouds and hot plasma. We also find that the gas pressure is roughly constant except for the three shock-engulfed clouds inside or on the SNR shell, suggesting that almost no clouds have evaporated within the short SNR age of ∼4800 yr. This result is compatible with the shock-interaction model with dense and clumpy clouds inside a low-density wind bubble.
CRIS-Team Scopus Importer:2024-12-16